The Intelligence Behind the Click: A Bibliometric Study of E-Commerce and Emerging Cognitive Technologies (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
In the digital era, online transactions are integral to everyday life—from grocery  shopping and clothing purchases to streaming services like Netflix and Amazon  Prime. E-Commerce has progressed beyond simple transactions, now leveraging  intelligent systems for personalized user experiences via recommendation  engines analyzing user behavior, reviews, and past transactions. This  transformation is largely powered by the integration of Artificial Intelligence  (AI), Machine Learning (ML), and Deep Learning (DL). Over the last decade,  this convergence has garnered substantial academic attention. This study presents a bibliometric analysis of 2,464 peer-reviewed publications  from 2018 to 2025, sourced from the Dimensions database and filtered through  the PRISMA framework and UGC CARE List-II criteria. The analysis explores  publication trends, influential authors and institutions, significant countries,  high-impact papers, and emerging thematic clusters. The findings reveal  an uptrend in research activity, heightened technological integration, and  shifting research priorities. The study offers a roadmap for future inquiry at the  intersection of E-Commerce and AI technologies.
Keywords: E-Commerce; Artificial Intelligence; Machine Learning; Deep Learning; Bibliometric Analysis; Research Trends; UGC CARE